SKIP is an indispensable factor for Caenorhabditis elegans development - Kostrouchova, Marta; Housa, Daniel; Kostrouch, Zdenek; Saudek, Vladimir; Rall, Joseph Edward (Proceedings of the National Academy of Sciences of the United States of America, 2002)
SKI-binding protein (SKIP) is a transcription cofactor present in all eukaryotes. Here we show that SKIP is a unique protein that is required for Caenorhabditis elegans viability and development. Expression of CeSKIP (skp-1) assayed by RT-PCR and by GFP fluorescence in transgenic lines starts in embryos and continues to adulthood. Loss of CeSKIP activity by RNA-mediated inhibition results in early embryonic arrest similar to that seen following inhibition of RNA polymerase II. RNA polymerase II phosphorylation appears normal early in CeSKIP RNA-mediated inhibition treated embryos although the expression of several embryonic GFP reporter genes is severely restricted or absent. Our data suggest that CeSKIP is an essential component of many RNA polymerase II transcription complexes and is indispensable for C. elegans development.
Keywords: RNA Polymerase II; RNA, Fungal; Helminth Proteins; Transcription Factors; larva; geneticky modifikovaná zvířata; jaderné proteiny; zvířata; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Gene Expression Regulation, Developmental; proteiny Caenorhabditis elegans; Animals, Genetically Modified; geny helmintů; RNA-polymerasa II; fungální RNA; komplexy ubikvitinligas; Nuclear Proteins; proteiny červů; Genes, Helminth; Ubiquitin-Protein Ligase Complexes; Larva; vývojová regulace genové exprese; transkripční faktory; Animals